1971
DOI: 10.1037/h0031333
|View full text |Cite
|
Sign up to set email alerts
|

Components of attention.

Abstract: The study of human attention may be divided into three components. These are alertness, selectivity, and processing capacity. This paper outlines experimental techniques designed to separate these components and examine their interrelations within comparable tasks. It is shown that a stimulus may be used to increase alertness for processing all external information, to improve selection of particular stimuli, or to do both simultaneously. Development of alertness and selectivity are separable, but they may go … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

38
795
8
13

Year Published

1990
1990
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,344 publications
(862 citation statements)
references
References 37 publications
38
795
8
13
Order By: Relevance
“…More precisely, functional independence means that This article explores the functional independence of stop and go processes by examining the hypothesis that they share capacity. Capacity sharing is a common explanation of dual-task interference (Kahneman, 1973;Pashler, 1994;Posner & Boies, 1971), and several studies have asked whether the stop process and the go process share capacity (Logan, 1981;Logan & Burkell, 1986;Yamaguchi, Logan, & Bissett, 2012). We ask the question more rigorously, using parameters of our stop-signal models to measure capacity and assess functional independence (Townsend & Ashby, 1983).…”
Section: Independence Assumptionsmentioning
confidence: 99%
“…More precisely, functional independence means that This article explores the functional independence of stop and go processes by examining the hypothesis that they share capacity. Capacity sharing is a common explanation of dual-task interference (Kahneman, 1973;Pashler, 1994;Posner & Boies, 1971), and several studies have asked whether the stop process and the go process share capacity (Logan, 1981;Logan & Burkell, 1986;Yamaguchi, Logan, & Bissett, 2012). We ask the question more rigorously, using parameters of our stop-signal models to measure capacity and assess functional independence (Townsend & Ashby, 1983).…”
Section: Independence Assumptionsmentioning
confidence: 99%
“…They differ primarily in the assumptions they invoke to explain the limit. Some theories assume that a limited capacity for activation constrains the number of items that can be kept sufficiently active to be recalled (Anderson, Reder, & Lebiere, 1996;Daneman & Carpenter, 1980;Just & Carpenter, 1992;Logan, 1978Logan, , 1979see Kahneman, 1973;Moray, 1967;Posner & Boies, 1971). Other theories assume that activation decays over time and only a limited number of items can be kept active enough to be recalled Baddeley, 1986Baddeley, , 1996Baddeley & Hitch, 1974;Cowan, 1995Cowan, , 1999Hitch, Towse, & Hutton, 2001).…”
Section: Capacity Limitations In Working Memorymentioning
confidence: 99%
“…Research reported since this time has also been the subject of periodic reviews (R. G. M. Morris, 1996; Parasuraman, in press;Parasuraman & Greenwood, 1998;Perry & Hodges, 1999), as have studies of attention in healthy aging McDowd & Shaw, 2000). Accordingly, we do not revisit this burgeoning literature but briefly survey the major results before focusing on two aspects of attentional function that have been shown to be sensitive to the ApoE gene and AD.Although there is no completely agreed on taxonomy of attention, a good case can be made for the relative independence of at least three components: selection, vigilance, and executive control (Parasuraman, 1998;Parasuraman & Davies, 1984;Posner & Boies, 1971). Selection refers to the preferential processing of particular stimuli that are relevant to an organism's current goal; vigilance ensures that processing is maintained over time so that the goal can be achieved; and executive control allows for the time sharing and coordination of these processing activities with other goal-directed activities (Parasuraman, 1998).…”
mentioning
confidence: 99%